Entrepreneurs and SMEs in Peru - Damián López, Víctor Gerónimo (2020)
The purpose of this research work was to demonstrate that SMEs, small and medium enterprises, are basic political organizations, the product of entrepreneurs and that, due to little or no State support, they operate in the informality of our economy. Regarding the methodology, the type of research is basic. The research design is non-experimental. The sample consisted of scientiﬁc articles. The instrument used was the documentary analysis guide. The investigation reached the following conclusions: The SMEs, small and medium enterprises in Peru, are basic economic organizations, product of the entrepreneur and that, due to little or no support of the State, they operate in the informality. Informality in Peruvian economy is structural.